Insect pest complex of brinjal and management of Leucinodes orbonalis at mid hills of Meghalaya - Pukhram Bhumita; D. Kumar (Umiam : CPGS, CAU, 2011)
Insect pest complex of brinjal was studied by recording number of insect pests on five randomly selected plants from each plot during 2010. The shoot and fruit borer was recorded in shoot by counting the dropped shoots and in fruits by counting the damaged fruits after cutting the fruits. The aphid, white fly and leaf miner were recorded on five leaves and for jassid, brinjal leaf beetle, red spider mite, thrips and white spotted flea beetle were recorded on three leaves (upper, middle, lower) on tagged plants. Insect pests recorded were identified and catalogued and deposited in the museum of Division of Entomology, ICAR Research Complex for NEH Region at Umiam, Ri-Bhoi, Meghalaya. The insect pests recorded during 2010 were aphids (Aphis gossypii Glover), jassids (Amrasca biguttula biguttula Ishida), brinjal leaf beetle (Phylliodes balyi), white spotted flea beetle (Monolepta signata Oliv), red spider mite (Tetranychus urticae Koch), thrips (Thrips tabaci Lind.), whitefly (Bemisia tabaci Lind.), leaf miner (Liriomyza trifolii Meigan), fruit and shoot borer (Leucinodes orbonalis Guen.). The natural enemy recorded was spider (Oxyopes javanus Thorell). The incidence of these pests was observed from first week of April, 2010 (crop age: 3 DAT) till crop maturity. Among the insect pests recorded, shoot and fruit borer was the major pest of brinjal. The abiotic factors were found to favour the incidence of red spider mite, white spotted beetle, leaf miner, shoot and fruit borer and spider. Incidence of jassids, leaf beetle, thrips, whitefly and aphids were independent of the weather factors. The management trials with different bio-rational insecticides and conventional insecticide revealed that endosulfan (0.07%) was the most effective in reducing the population of Leucinodes orbonalis in shoots, followed by spinosad (75 g a.i./ha) and pheromone (100 traps /ha) in their order of efficacy. Whereas pheromone was superior followed by endosulfan and spinosad in reducing the pest population in fruits. The efficacy of endosulfan (Thiodan 35% EC), pheromone (Luci lure) and spinosad (Spintor 45 SC) were at par in controlling the pest. Endosulfan was toxic to the natural enemies, whereas, spinosad waS' less toxic to the natural enemies. Both the botanicals and microbials were safe to the natural enemy. Among all the management techniques, pheromone treated plot gave the highest yield.
Keywords: Leucinodes orbonalis; Brinjal-insect pests